2018
DOI: 10.15344/2455-2364/2018/137
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Maternal and Neonatal Vitamin B12 Serum Levels in Full Term Neonates with Physiologic Jaundice

Abstract: Introduction: Vitamin B12 (vitB12)deficiency causes failure of red blood cells (RBC) maturation leading to cell lysis causing excess heme production resulting in indirect hyperbilirubinemia.Purpose: We aimed toassess vitB12 serum levels in neonates with jaundice and compare these levels with that of apparently healthy neonates and detect the impact of the maternal vitB12 on both vitB12 and bilirubin of their neonates.Patients and methods: Complete blood count (CBC), C-reactive protein (CRP), and VitB12 were as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Aziz and Elela demonstrated that the vitamin B12 level of newborns with jaundice was significantly lower than healthy controls. 9 Maternal vitamin B12 is positively correlated with neonatal vitamin B12 and negatively correlated with neonatal total serum bilirubin levels. 9 In the present study, serum vitamin B12 levels in infants with prolonged jaundice and undetermined etiology were significantly lower in the study group.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Aziz and Elela demonstrated that the vitamin B12 level of newborns with jaundice was significantly lower than healthy controls. 9 Maternal vitamin B12 is positively correlated with neonatal vitamin B12 and negatively correlated with neonatal total serum bilirubin levels. 9 In the present study, serum vitamin B12 levels in infants with prolonged jaundice and undetermined etiology were significantly lower in the study group.…”
Section: Discussionmentioning
confidence: 97%
“…Aziz and Elela demonstrated that the vitamin B12 level of newborns with jaundice was significantly lower than healthy controls. 9 Maternal vitamin B12 is positively correlated with neonatal vitamin B12 and negatively correlated with neonatal total serum bilirubin levels. 9…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations